Fire-crested alethes (Alethe castanea) follow humans and bushbuck in Uganda’s Budongo Forest - Freymann, Elodie; Taylor, Derry (Frontiers in Bird Science, 2025)
This report documents four observations of a novel foraging behavior in fire-crested alethes (Alethe castanea) in the Budongo Forest Reserve of Western Uganda, where the birds were observed following humans and bushbuck, likely to flush out insect prey, diverging from their typical ant-following strategy. These observations expand our understanding of commensal relationships in tropical forest ecosystems and highlight the adaptability of bird foraging strategies.